Um Estudo Químico-quântico da Covalência Intermolecular em Sistemas Estabilizados por Ligações de Hidrogênio π∙∙∙H e N∙∙∙H: Cálculos DFT, ChelpG, NBO e QTAIM - Danilo Guimarães do Rego; Boaz Galdino de Oliveira (Orbital: The Electronic Journal of Chemistry, 2016)
In this work, density functional calculations at BHandHLYP/6-311++G(d,p) theoretical level of structural parameters, electronic properties and vibration modes of the C2H2∙∙∙HCN∙∙∙HF and C2H4∙∙∙HCN∙∙∙HF T-shaped hydrogen complexes is presented. As is well-known, the formation of these complexes is ruled by weak and strong hydrogen bonds recognized as p∙∙∙H and N∙∙∙H, respectively. In line with this interaction strength, a correlation between the structural modifications and frequency shifts was investigated, although the non-covalent character of these complexes has been unveiled through the QTAIM calculations. The absorption intensity ratios of the proton donors correlate well with the charge transfer amounts, whose values were computed through the ChelpG approach. Even by taking into account the cooperative profile of these systems, the hydrogen bond energies were determined, and actually, the values are unapproachable to be distributed in different moieties, such as punctual strong hydrogen bonds possessing covalent character, if exist. At last, the NBO calculations were applied to compute the s- and p-contributions on the hybrid orbitals in order to explain the frequency shifts on the H–C and H–F proton donor bonds.DOI: http://dx.doi.org/10.17807/orbital.v1i1.705